A Survey of Provider Attitudes, Beliefs, and Perceived Barriers Regarding a Centralized Direct-Mail Colorectal Cancer Screening Approach at Community Health Centers - Jamie H. Thompson; Jennifer L. Schneider; Jennifer S. Rivelli; Amanda F. Petrik; William M. Vollmer; Morgan J. Fuoco; Gloria D. Coronado (SAGE Publishing, 2019)
Background: Colorectal cancer screening (CRC) rates are low, particularly among individuals with low socioeconomic status. Organized CRC screening programs have demonstrated success in increasing screening rates. Little is known about provider attitudes, beliefs, and practices related to CRC screening or how they are influenced by an organized CRC screening program. Methods: In 2014 and 2016, providers from 26 safety net clinics in Oregon and Northern California were invited to complete baseline and follow-up online surveys for the Strategies and Opportunities to Stop Colon Cancer in Priority Populations (STOP CRC) study. The provider survey link was sent electronically to primary care providers serving adult patients. Providers were sent reminders every 2 weeks via email to complete the survey, up to 3 reminders total. In this article, we describe learnings about provider attitudes, beliefs, and practices related to CRC screening after implementation of the STOP CRC program. Results: A total of 166 unique providers completed baseline and/or follow-up surveys, representing 228 responses. Main themes included (1) favorable shifts in attitude toward fecal immunochemical test (FIT) and direct-mail cancer screening programs, (2) changes in provider perception of key barriers, and (3) growing interest in centralized automated systems for identifying patients due for CRC screening and eligible for population-based outreach. Discussion: Providers are interested in improved information systems for identifying patients due for CRC screening and delivering population-based outreach (ie, to distribute FIT kits outside of the clinic visit) to help reduce health system- and patient-level barriers to screening. Trial Registration: National Clinical Trial (NCT) Identifier NCT01742065.